(untitled) (Eurasian Journal of Philology Science and Education, 2021)
The epic tradition of the Kazakh people is based on an ethnic process that spans many centuries. Therefore, the epic tradition that has reached us from the depths of centuries is not only an artistic, but also a cognitive phenomenon. The epic and epic tradition developed in those regions where active historical and ethnic processes took place, which left their traces in the consciousness of the people. In the article, the epic tradition is evaluated as a phenomenon of the ethnographic order, and the heroic epic is a symbiosis of poetry and music. Much has been said about the role of carriers of the musical and poetic traditions of the Kazakh people – zhyrau and zhyrsha, which were described either as an improviser or as a simple performer. Some authors claimed that the Zhyrau disappeared after the XYIII century and only the Zhyrsha remained. However, such a statement of the question was poorly reasoned. After all, it is well known that despite the above judgments, individual representatives of the epic tradition throughout the 19th century were called zhyrau (Bazar-zhyrau). The article focuses on the fact that the epic tradition of the Kazakh people was studied very disparately, without taking into account the syncretic unity of the cognitive and poetic sphere. It is noted that such surveys did not lead to the creation of a holistic picture of the epic world of Kazakhs. This is the synergistic nature of the problem.